2012
DOI: 10.4137/bcbcr.s9607
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Breast Cancer-Associated Lipids in Scalp Hair

Abstract: A correlation between the presence of breast cancer and a change in the synchrotron-generated X-ray diffraction (XRD) pattern of hair has been reported in several publications by different groups, and on average XRD-based assays detect around 75% of breast cancer patients in blinded studies. To date, the molecular mechanisms leading to this alteration are largely unknown. We have determined that the alteration is likely to be due to the presence of one or more breast cancer-associated phospholipids. Further ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…These data were compatible with those obtained by previous study using synchrotron source which, rings related to d-spacing of hair structure have been reported (9)(10)(11)(12)(13) . But, as shown in *igure 3, there was an additional ring re*lects 4.7 nm d-spacing in cancer patients (12,14) . The 9.8 AE re*lection dspacing refers to structure pattern of the alphahelix diameter and the 4.4 AE re*lection is referring to the periodic distance of the 3.6-alpha-helix structure (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were compatible with those obtained by previous study using synchrotron source which, rings related to d-spacing of hair structure have been reported (9)(10)(11)(12)(13) . But, as shown in *igure 3, there was an additional ring re*lects 4.7 nm d-spacing in cancer patients (12,14) . The 9.8 AE re*lection dspacing refers to structure pattern of the alphahelix diameter and the 4.4 AE re*lection is referring to the periodic distance of the 3.6-alpha-helix structure (18) .…”
Section: Discussionmentioning
confidence: 99%
“…They reported that synchrotron-derived X-ray diffraction has the potential ability to provide a non-invasive method to show the presence of breast cancer (13) . Several studies by other researchers con*irmed an association between the XRD hair patterns and the presence of breast cancer (14) . Limitations including of the complexity of interpretation the data and lack of synchrotron based on X-ray diffraction apparatus in all medical experiments centers, caused evaluation of XRD patterns using a facility other than synchrotron.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a noninvasive method of breast cancer detection in patient hair using a non‐synchrotron based X‐ray diffraction method has been described . Interestingly, Fourier transformed infra‐red spectroscopy has also been used to identify breast cancer specific lipid changes . Also, analysis of hair sample from a patient with Ribosomopathy by X‐ray diffraction revealed structural abnormalities .…”
Section: Structural Proteomics Of Hairmentioning
confidence: 99%
“…The alpha‐helical secondary structure of hair keratin intermediate filaments accounts for the appearance of a XRD ring pattern with a molecular spacing of 4.76 ± 0.07 nm in the hair of breast cancer patients (James, ). The presence of breast cancer‐associated phospholipids was identified using XRD and solvent extraction of lipids (Mistry et al, ). Attenuated total reflection Fourier transform infrared (ATR‐FTIR) studies (Lyman and Murray, , Lyman and Fay, ) demonstrated structural features and compositional abnormalities of hair samples from breast cancer patients, which may indicate an increase in β‐sheet disorder and lipid content by changes in the CH overtone region and the amide I region of the FTIR spectrum, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the X-ray diffraction (XRD) patterns of hair from individuals with breast cancer, there is the presence of ring, in contrast to healthy subjects (James et al, 1999), and much evidence supporting the finding has accumulated through the investigation of the molecular nature of the structural alteration (James, 2011;Mistry et al, 2012) and clinical testing (Corino and French, 2008;Corino et al, 2009) despite controversy regarding overall accuracy (Briki et al, 1999) and uncorrelated BRCA 1/2 mutations (Laaziri et al, 2002). The alpha-helical secondary structure of hair keratin intermediate filaments accounts for the appearance of a XRD ring pattern with a molecular spacing of 4.76 6 0.07 nm in the hair of breast cancer patients (James, 2011).…”
Section: Introductionmentioning
confidence: 99%